Microbial contributions to sustainable paddy straw utilization for economic gain and environmental conservation - Baljeet Singh Saharan; Deepika Dhanda; Neelam Kumari Mandal; Ramesh Kumar; Deepansh Sharma; Pardeep Kumar Sadh; Dilfuza Jabborova; Joginder Singh Duhan (Current Research in Microbial Sciences)
Paddy straw is a versatile and valuable resource with multifaceted benefits for nutrient cycling, soil health, and climate mitigation. Its role as a rich nutrient source and organic matter significantly enhances soil vitality while improving soil structure and moisture retention. The impact of paddy straw extends beyond traditional agricultural benefits, encompassing the promotion of microbial activity, erosion control, and carbon sequestration, highlighting its crucial role in maintaining ecological balance. Furthermore, the potential of paddy straw in bioenergy is explored, encompassing its conversion into biogas, biofuels, and thermal energy. The inherent characteristics of paddy straw, including its high cellulose, hemicellulose, and lignin content, position it as a viable candidate for bioenergy production through innovative processes like pyrolysis, gasification, anaerobic digestion, and combustion. Recent research has uncovered state-of-the-art techniques and innovative technologies capable of converting paddy straw into valuable products, including sugar, ethanol, paper, and fiber, broadening its potential applications. This paper aims to underscore the possibilities for value creation through paddy straw, emphasizing its potential use in bioenergy, bio-products, and other environmental applications. Therefore, by recognizing and harnessing the value of paddy straw, we can advocate for sustainable farming practices, reduce waste, and pave the way for a resource-efficient circular economy. Incorporating paddy straw utilization into agricultural systems can pave the way for enhanced resource efficiency and a more sustainable circular economy.